A simulation-based dynamic scheduling model for curtain wall production considering construction planning reliability. (1st March 2021) - Kim, Taehoon; Kim, Yong-Woo; Cho, Hunhee
Abstract: Appropriate production scheduling of curtain wall systems is essential for the successful completion of construction projects. The construction process of the curtain wall system is mainly on the critical path and accounts for 10–15% of the total construction cost. Should curtain wall products not be timeously delivered to the construction site, construction projects are likely to fall behind schedule with most relevant activities on curtain wall installation on a critical path. However, due-date uncertainty caused by a contractor's lack of planning reliability causes the curtain wall production schedule to become complex and changes the due date after the initial order. In this regard, this study proposes a discrete event simulation-based dynamic scheduling model for curtain wall production to deliver products on time to the construction site by considering each construction project's planning reliability. Through simulation experiments, the validity and effectiveness of the proposed model were tested. The results of this study will help the successful completion of construction projects by ensuring the progress of the curtain wall system construction and follow-up activities following the construction schedule. Highlights: Construction planning reliability affects curtain wall production schedule. A scheduling model considering construction planning reliability was proposed. Performance of the model was tested on 25 scenarios compared to other dispatching rules. The model showed better performance than other dispatching rules in most of the scenarios.